Marketing policies and their impact on attracting new customers (applied to Sin Flour Mills Company, Atbara), Sudan - Ali, Mohamed Ibrahim Mohamed (Journal of Economic, Administrative and Legal Sciences, 2025)
The aim of this study is to analyze the impact of marketing policies on attracting new customers, with a practical application on Senn Mills for Grains in Atbara. Marketing policies are considered one of the main factors influencing the success of companies in increasing their market share and enhancing customer loyalty, especially in competitive sectors such as the grain industry. The research problem revolves around whether marketing policies are capable of attracting new customers and whether promotional policies are the most influential in this regard. Additionally, the study examines the impact of the non-storability of services on the company's losses. The significance of the research lies in understanding the role of marketing policies in striving to meet customer needs and the importance of having convincing marketing approaches for new customers. The study is based on the hypothesis that there is a positive relationship between marketing policies and the ability to attract customers. It also identifies the challenges the company faces in implementing effective marketing policies. The study adopted a mixed research methodology, combining quantitative and qualitative analysis, through interviews with marketing officials in the company to understand their marketing strategies and the challenges they encounter. The results showed that marketing policies focusing on product quality and meeting customer needs were the most effective in attracting new customers. Additionally, the use of social media platforms and digital advertising significantly contributed to reaching potential customers.
Keywords: Marketing policies; attracting new customers; digital marketing; promotion and advertising marketing strategies